Digitalisasi dan Pengembangan Pemasaran, Operasional, dan Keuangan UMKM Zean Store - Constantin, Evangelina Yovela; Sungadi, Tiffany Elizabeth; Stephen, Stephen; Christian, Hensel; Loyangjaya, Julius Benedict; Tumegah, Steven Hartono; Jan, Agnes Dharmasaputra; Ivanka, Zanetha; Ramadhanti, Fati (Journal Pemberdayaan Masyarakat Indonesia, 2024)
The COVID-19 pandemic has accelerated digitalization in Indonesia, including for Micro, Small, and Medium Enterprises (MSMEs). Zean Store, a Muslim clothing MSME in Cilimus, Kuningan, faced challenges in digitalization due to limitations in time, knowledge, and local competition. A mentoring program was implemented to enhance marketing through social media (Instagram, TikTok), open an online store on Shopee, and adopt a simple bookkeeping system using Google Sheets. The results of the mentoring showed improvements in brand awareness, operational efficiency, and sales. This study emphasizes the importance of digitalization for the advancement of MSMEs in the digital era.